2015
DOI: 10.1016/j.snb.2015.06.068
|View full text |Cite
|
Sign up to set email alerts
|

Interferometric-type optical biosensor based on exposed core microstructured optical fiber

Abstract: In all cases accepted manuscripts should:  link to the formal publication via its DOI  bear a CC-BY-NC-ND license -this is easy to do, click here to find out how  if aggregated with other manuscripts, for example in a repository or other site, be shared in alignment with our hosting policy  not be added to or enhanced in any way to appear more like, or to substitute for, the published journal article Abstract: This work presents a novel biosensor using the multimode interference effect in an exposed core m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…FFT techniques are widely used for de-multiplexing interference spectra [25,26], which is more precise than other methods of tracking interference spectrum shifts, such as peak tracking or function fitting [27]. The value of the phase () is taken from the complex value at the FFT peak.…”
Section: Operating Principlementioning
confidence: 99%
See 1 more Smart Citation
“…FFT techniques are widely used for de-multiplexing interference spectra [25,26], which is more precise than other methods of tracking interference spectrum shifts, such as peak tracking or function fitting [27]. The value of the phase () is taken from the complex value at the FFT peak.…”
Section: Operating Principlementioning
confidence: 99%
“…While it is in principle possible to measure both parameters simultaneously using the higher order mode FBG reflections, the sensor had relatively poor sensitivity to RI the order of only 1-5 nm/RIU [1,24]. We have since shown that interferometric based exposed-core fiber sensors can offer high RI sensitivity [25,26], such as 667 nm/RIU in a multimode Mach-Zehnder configuration [25].…”
Section: Introductionmentioning
confidence: 99%
“…The region where the evanescent field propagates determines the interaction volume between the light and the surrounding medium. This accessible interaction volume allowed a wide variety of applications including sensors for biology [18,19]. For example, exposed-core fibers have been used for the detection of fluorescence signals [20,21] and for detection of label-free molecule ensembles in an interferometric configuration [18,19].…”
Section: Exposed-core Fibersmentioning
confidence: 99%
“…Demonstrated sensing configurations and applications are diverse, including: hydrogen peroxide sensing using Raman scattering [19], fluorescent indicator coatings for detection of aluminum [20] and calcium and cadmium ions [21], absorption spectroscopy of biomolecules [22], and the use of fluorescent labeling techniques for antibodies [23] and proteins [24]. There are also numerous examples of microstructured optical fiber sensing techniques that measure changes in the refractive index of the material filled into the fiber holes [14], such as: techniques based on multimode interferometry [25], multi-core mode-coupling [26], and surface plasmon resonance [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%